2015
DOI: 10.1111/mcn.12242
|View full text |Cite
|
Sign up to set email alerts
|

Using implementation research for evidence‐based programme development: a case study from Kenya

Abstract: The few available studies of programme effectiveness in nutrition find that programmes are less effective than would be predicted from the efficacy trials that are the basis for evidence‐based programming. Some of these are due to gaps in utilisation within households. To a greater extent, these gaps can be attributed to problems in programme design and implementation. ‘Implementation research in nutrition’ is an emerging area of study aimed at addressing this problem, by building an evidence base and a sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…Our findings corroborate those of other studies [8][9][10][11]15 that underscore the importance of the role of context in designing IYCF interventions. However, as in the FES in Kenya, 11,15 these studies not only identified 2 major sets of barriers and challenges to the adequacy of IYCF, they also revealed several positive elements of caregiver beliefs and behaviors, presenting opportunities to adapt or introduce context appropriate interventions to improve IYCF in these distinct agrarian Ghanaian populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings corroborate those of other studies [8][9][10][11]15 that underscore the importance of the role of context in designing IYCF interventions. However, as in the FES in Kenya, 11,15 these studies not only identified 2 major sets of barriers and challenges to the adequacy of IYCF, they also revealed several positive elements of caregiver beliefs and behaviors, presenting opportunities to adapt or introduce context appropriate interventions to improve IYCF in these distinct agrarian Ghanaian populations.…”
Section: Discussionsupporting
confidence: 90%
“…Formative research is recognized as a tool that provides context-specific data to inform evidencebased decisions for nutrition and public health interventions. [8][9][10][11] It is particularly valuable in identifying suitable interventions or potential barriers that are likely to affect the success of an intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these questions, the closely related topics of what proportion of IYC diets are composed of complementary feeding cultural core foods (if any), as distinct from household foods, and the process of integration of IYC into household diet, lie outside the scope of this paper and are not addressed here. To examine the four questions, we draw from the database of ethnographic and dietary information that was generated in a multisite study in Kenya, which was part of a multidisciplinary research effort to produce a landscape analysis that could be used to inform the development of interventions to improve nutrition of children and women (Pelto & Thuita, 2016;Tumilowicz, McClafferty, Neufeld, Hotz, & Pelto, 2015). Following the FES manual, the study design entailed a two-phase study in which key informants were interviewed in Phase I to obtain basic information on IYCF.…”
Section: Key Messagesmentioning
confidence: 99%
“…To address the broad question—“Is there a complementary feeding cultural core in rural Kenya?”—we identified four specific questions: Is there consensus about what foods are fed to infants and young children? Do infants and young children receive foods that are specially purchased and/or prepared for them? Are specially prepared foods shared with other members of the household? Are there any foods prepared for household consumption that are not shared with IYC? In addition to these questions, the closely related topics of what proportion of IYC diets are composed of complementary feeding cultural core foods (if any), as distinct from household foods, and the process of integration of IYC into household diet, lie outside the scope of this paper and are not addressed here. To examine the four questions, we draw from the database of ethnographic and dietary information that was generated in a multisite study in Kenya, which was part of a multidisciplinary research effort to produce a landscape analysis that could be used to inform the development of interventions to improve nutrition of children and women (Pelto & Thuita, ; Tumilowicz, McClafferty, Neufeld, Hotz, & Pelto, ).…”
Section: Introductionmentioning
confidence: 99%